Leveraging Education through Artificial Intelligence Virtual Assistance: A Case Study of Visually Impaired Learners - Ice Mae Solon; Fatima Rose Sanchez; Tristan Kent Delante; Jean Kathleen Villegas; Florence John Basay; Jay-r Andales; Francine Pasko; Mary Fair Ruval Estrera; Roberto Samson Jr.; Romel Mutya; Paul NiÃ±o Ry Mina (International Journal of Educational Innovation and Research, 2023)
The study aims to explore an in-depth analysis of leveraging education through artificial intelligence (AI) virtual assistance among visually impaired learners. The investigation centers on describing the challenges and struggles encountered by visually impaired learners, highlighting the usage of AI virtual assistance, the adaptability of the visually impaired learners, and the enhancement of the curriculum. This study utilized a qualitative case study research design using Braun and Clarkeâ€™s (2008) data analysis method to describe an in-depth dissection of a case study involving five visually impaired learners through semi-structured interviews. Findings revealed five themes: (1) barriers in the learning process, (2) essentiality of AI virtual assistants, (3) achieving competence through technology, and (4) inclusive teaching and learning environment. The findings show that this pandemic has brought challenges to visually impaired learners in education, such as personal struggles, insufficiency of resources, and adapting to new learning modalities. However, AI virtual assistance allowed them to explore their potential and help them achieve academic tasks that are generally difficult due to their visual impairment. Researchers recommend improving the teaching and learning of visually impaired students in secondary schools.